2008
DOI: 10.1097/olq.0b013e3181644b9c
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Prevalent and Incident Trichomonas vaginalis Among Women Attending Three Sexually Transmitted Disease Clinics

Abstract: T. vaginalis incidence is high in women. Risk factors for prevalent and incident infection are similar. T. vaginalis was associated with older age in women, unlike other sexually transmitted infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
36
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 16 publications
6
36
6
Order By: Relevance
“…27 We found that women who had no school-based education, women who lived in slums and women whose husbands were in polygamous marriages were more likely to have trichomoniasis and that these findings were supported by other studies. 12,28 Our finding that cervical STIs were associated with suspected infidelity is also supported by previous studies. 12 The findings of this study may not be generalized to all married women complaining of vaginal discharge.…”
supporting
confidence: 80%
“…27 We found that women who had no school-based education, women who lived in slums and women whose husbands were in polygamous marriages were more likely to have trichomoniasis and that these findings were supported by other studies. 12,28 Our finding that cervical STIs were associated with suspected infidelity is also supported by previous studies. 12 The findings of this study may not be generalized to all married women complaining of vaginal discharge.…”
supporting
confidence: 80%
“…Previous studies have suggested that differences in vaginal bacterial communities exist among Caucasian and black women (8,18). These data coupled with the known disparities that exist between black women and women of other races and their susceptibility to BV, herpes simplex virus (HSV), and other STIs, may account for the increased acquisition of S. pseudoporcinus observed (2,4,8,9,11,12).…”
Section: Discussionmentioning
confidence: 59%
“…T. vaginalis, C. trachomatis, and N. gonorrhoeae prevalences were highest in black populations, a trend documented in the U.S. population for T. vaginalis as well as for C. trachomatis and N. gonorrhoeae (1,9,11,15,17,29). NHANES found the highest T. vaginalis rates in non-Hispanic black women (13.3%), and within this group, T. vaginalis rates increased from 8.3% (14 to 19 years) to almost 20% (40 to 49 years) (1).…”
Section: Discussionmentioning
confidence: 92%